Bioaccumulation, physiological and ultrastructural effects of glyphosate in the lichen Xanthoria parietina (L.) Th. Fr. (December 2016) - Vannini, Andrea; Guarnieri, Massimo; Paoli, Luca; Sorbo, Sergio; Basile, Adriana; Loppi, Stefano
Abstract: This study compared bioaccumulation as well as physiological (content of ergosterol as marker of fungal vitality and photosynthetic efficiency as marker of algal vitality) and ultrastructural effects of glyphosate in the lichen Xanthoria parietina, with the herbicide being provided either by soaking or spraying of the samples. The results showed that bioaccumulation of glyphosate is fast and proportional to the dose supplied, and is independent on the way it is supplied. Toxic effects resulting from glyphosate uptake by both soaking and spraying were evident at physiological and ultrastructural level, both in the algal and fungal partner, with negative effects being generally dose- and time-dependent. Since our results showed that the concentration of glyphosate bioaccumulated in X. parietina remains stable (at least up to 90 days), a perspective is open for using lichens in biomonitoring of atmospheric pollution by glyphosate as a side effect of the application of this herbicide. Highlights: Accumulation of glyphosate in lichens is fast and proportional to the dose supplied. Toxic effects are evident at physiological and ultrastructural level. Toxic effects are generally dose- and time-dependent. Glyphosate content in lichens remains stable up to 90 days. A perspective is open for using lichens in biomonitoring glyphosate air pollution.